All that it takes - Deese, Nicole (Bethany House, 2022)
"After moving cross-country with her son and accepting a filmmaker's mentorship, Val Locklier is caught between her insecurities and new possibilities. Miles McKenzie returns home to find a new tenant is living upstairs and he's been banished to a ministry on life support. As sparks fly, they discover that authentic love and sacrifice must go hand in hand"--